PELANGGARAN HAK ASASI MANUSIA (HAM) TERHADAP TENAGA KERJA INDONESIA (TKI) DI MALAYSIA TAHUN 2011-2013 - DS, Desideria Talitha; Windiani, Reni; P, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Malaysia is a main destination for Indonesian labors in Southeast Asia.Indonesian Labors that worked in Malaysia wanted to fix their family’seconomy condition, but their existence is thus vulnerable to human rightsviolations in particular domestic workers sector. Cases of human rightsviolations experienced by Indonesian Labors in Malaysia include traffickingin persons for labor which is a form of transnational crime. This researchaims to know the human rights violations experienced by the labor ofIndonesia in Malaysia period 2011-2013. This research is using a qualitativemethod with descriptive research analytical techniques type through researchstudies of the literature and interviews. This research uses the concept ofhuman rights and theory of transnational crime in liberalism paradigm. Theresults obtained from this research indicate that human rights violationsexperienced by Indonesian labor domestic workers sector in Malaysiahappened during the pre-labor placement and the placement period.